Anthrone-based Dummy Molecularly Imprinted Polymer for the Selective Detection of Fluorene and Phenanthrene in Simulated River Water - Pinandita, Aria; Handayani, Nurrahmi; Iqbal, Muhammad; Triadhi, Untung; Rusnadi, Rusnadi; Djajanti, Samitha Dewi; Amran, Muhammad Bachri; Zulfikar, Muhammad Ali (Makara Journal of Science, 2026)
A dummy-template molecularly imprinted polymer (DMIP) was synthesized via precipitation polymerization using anthrone as a template analog for the selective analysis of low-molecular-weight polycyclic aromatic hydrocarbons (PAHs), specifically fluorene and phenanthrene. Styrene, benzoyl peroxide, and ethylene glycol dimethacrylate were employed as the functional monomer, radical initiator, and crosslinking agent, respectively. The synthesized polymers were characterized by Fourier-transform infrared spectroscopy, scanning electron microscopy, and particle size analysis. The imprinting factors were 1.16 and 1.09 for fluorene and phenanthrene, respectively, indicating enhanced affinity of the imprinted sites. High-performance liquid chromatography analysis following DMIP-based solid-phase extraction yielded recoveries of 91.49% ± 3.87% for fluorene and 97.25% ± 2.85% for phenanthrene, demonstrating the DMIP’s potential as an efficient sorbent for selective extraction and quantification of low-molecular-weight PAHs in simulated river water.